Effects of co-precipitation method on microwave dielectric properties of 0.7CaTiO3-0.3SmAlO3 ceramics - Huajian Hu; Chun-E Huang; Jing Nan; He Wang; Chunying Shen (Materials Research Express, 2020)
The effects of co-precipitation method on densification, microstructure, phase composition and dielectric properties of 0.7CaTiO _3 –0.3SmAlO _3 ceramics (CTSA) have been studied. Compared with the traditional solid-phase method, the co-precipitation method effectively reduced the calcining temperature of CaTiO _3 powders and SmAlO _3 powders from 1250 to 900 °C and reduced the sintering temperature of CTSA ceramics from 1470 to 1380 °C. The sintering and dielectric properties were improved. In particular, the Q  ×  f value was found to increase from 47 056 to 51 507 GHz and the τ _f reduced from +8.2 to +6.3 ppm °C. The CTSA ceramics, which were prepared by co-precipitation method sintered at 1380 °C for 3 h, possessed good and reasonable microwave dielectric properties: ε _r = 44.85, Q  ×  f  = 51 507 GHz ( f  = 6.45 GHz), τ _f  = +6.3 ppm °C.